Sistem Informasi E-Learning Berbasis Web pada SMPN 1 Rasau Jaya Kalimantan Barat - Hertyana, Hylenarti; Karo Karo, Alhazri; Rahmawati, Eva; Mufida, Elly (LPPM UNIKA Santo Thomas, 2022)
The Covid -19 pandemic has disrupted the conventional learning process. So a solution is needed to answer these problems, one of which is using information technology. The use of information technology media in the teaching and learning process is expected to arouse students' desire and interest in learning, generate motivation and stimulation of learning activities, and even bring psychological effects on students. E-learning is an electronic teaching and learning method that allows the delivery of teaching materials using the internet, intranet, or other media. Therefore, the author makes a information system design e-learning website base dusing the waterfall method in which there are stages of system requirements analysis, design, code generation, and testing. Later, after application -e-learning this website based through testing, black box there will be several features such as sharing materials, assignments and exam work online that is carried out directly in this application, so that learning with the method is e-learning expected to be one of the best solutions for solve the problems that existed during the pandemic covid-19 that disrupted the teaching and learning process at SMPN 1 Rasau Jaya, this is because learning with the method e-learning can allow teachers and students to interact insubjects online which can be accessed from their respective homes. so that the spread of thevirus Covid-19 can be further suppressed and prevented.